Numerical modeling of fatigue fracture in the light alloys produced by additive technology - Nikitin, Il′ya Stepanovich; Golubev, Vasiliy Ivanovich; Nikitin, Aleksandr Dmitriyevich; Stratula, Boris Andreyevich (Computational Continuum Mechanics, 2025)
A new approach to optimization of process parameters of selective laser melting is proposed in this paper. The required fatigue life of the final SLM product is used as an optimization parameter. A two-stage algorithm is proposed to implement this approach. At the first stage, a three-dimensional non-stationary nonlinear problem of heat conduction for a multiphase system is solved. As a result of modeling, geometric parameters of single-layer and multilayer systems of overlapping tracks are determined. The influence of laser melting process parameters (power, speed, laser beam pitch) on the topological features of the formed microstructure is studied. Characteristic types and geometric parameters of quasi-regular defects of the material produced by selective laser melting in the form of "unmelted" and multiple "overmelted" areas are obtained. At the second stage, the influence of single and multiple defects on the fatigue strength of printed samples under high-frequency loading is studied using the previously proposed multi-mode fatigue failure model. It is shown that internal heterogeneity of the microstructure of materials printed by selective laser melting can lead to earlier subsurface initiation of fatigue cracks and significantly reduce the fatigue strength and durability of the product. This effect is more pronounced for systems of multiple defects. The proposed models and calculation algorithms allow calculating the fatigue strength and durability of samples or products obtained by selective laser melting, depending on the selected process parameters. Mathematical modeling and comparison of the fatigue life of corset samples obtained by selective laser melting with experimental data are carried out. Qualitative and quantitative correspondence between the modeling and experimental results is noted.